The Force Levels Required to Mechanically Debond Ceramic Brackets: An In Vitro Comparative Study - Arici, S; Minors, C (Oxford Univ Press, 2000)
The in vitro force levels generated by four differing methods of mechanical debonding techniques for ceramic brackets, using debonding pliers, were measured. The forces generated using wide (method W) and narrow blades (method N) were compared with those generated using a diagonally opposite corner application of the wide blades (method C) and incisal-gingival application of a pair of pointed blades (method P). Chemically retained ceramic brackets (Transcend) were bonded to bovine teeth using a filled, two-paste, chemically cured composite (Concise). After 24 hours storage at 37 degrees C in water, each specimen was subjected to one of the four mechanical debonding methods in a custom-built jig, simulating the clinical application of conventional debonding pliers. A one-way ANOVA with a Tukey's honestly significant difference test revealed statistically significant differences in debonding strengths between the four methods at the 0.05 level of significance. The mean debonding strength generated by method C was 40 and 25 per cent lower than that for methods W and N, respectively. Scoring of the adhesive remnant index (ARI) revealed that the predominant bond failure site was at the bracket/adhesive interface for all groups. Macroscopically, no enamel damage or bracket fractures were observed.